Big cats (Carnivora, Felidae) still walking in Sierra de las Minas Biosphere Reserve: a forgotten Jaguar Conservation Unit in northeastern Guatemala - Trujillo, Luis A.; Mármol-Kattán, Alejandro; Abugarade, Cristina; Rivera-Sandoval, Adriana; Escobar-Anleu, Bárbara I.; y otros más. (2025)
The detection of Jaguars, Panthera onca (Linnaeus, 1758), and Pumas, Puma concolor (Linnaeus, 1771), in the Sierra de las Minas Biosphere Reserve, northeastern Guatemala, represents a pivotal step in understanding the distributional range of these apex predators in the country. Using camera traps, we documented 12 independent records of Puma and one of Jaguar, including the remarkable presence of Jaguars at elevations above 2000 m, which suggests new directions for ecological research and high-altitude conservation strategies. These findings have important implications for the long-term survival and conservation of these species within Jaguar Conservation Units, emphasizing the necessity of effective management measures that promote functional connectivity through habitat preservation and restoration, especially for populations outside the Mayan Biosphere Reserve.